Development and control of an articulated mobile robot T2 snake-4.2 for plant disaster prevention – development of M2 arm and C-hand. (2nd November 2022) - Chin, Ching Wen; Nakajima, Mizuki; Furuike, Koki; Kon, Kazuyuki; Tanaka, Motoyasu
ABSTRACT: In this study, we develop an articulated mobile robot T 2 Snake-4.2 that can move in narrow spaces, climb stairs, gather information, and operate valves for plant disaster prevention. We developed a novel folding arm M2 arm, fitted to the articulated mobile robot to have a better performance in mobility and operation ability compare to previous work T 2 Snake-4. We introduce a novel method of climbing high steps and stairs by using the M2 arm as a support for the articulated mobile robot. T 2 Snake-4.2 can climb high steps and stairs even with a heavy folding arm. In addition, we present a novel valve operating end effector, C-hand which allows the articulated mobile robot to open a large valve. By utilizing the shape characteristic of the valve, C-hand constraints to the environment and rotates the valve handle without transferring any reaction force to the robot and the folding arm. The developed robot T 2 Snake-4.2 is tested through experiments in the laboratory and also in a field test at the Plant Disaster Prevention Challenge of World Robot Summit 2020. GRAPHICAL ABSTRACT: UF0001